Effects of endogenous inhibitors on the evolution of antibiotic resistance genes during high solid anaerobic digestion of swine manure. (December 2018) - Sui, Qianwen; Meng, Xiaoshan; Wang, Rui; Zhang, Junya; Yu, Dawei; Chen, Meixue; Wang, Yawei; Wei, Yuansong
Graphical abstract: Highlights: The ARG properties during the HSAD largely differed with the low TS treatment. The shifts of ARGs were divided into three phases. VFAs, Proteobacteria and int I1 gave rise to the ARG increment. FA inhibition and VFA accumulation delayed and restricted the decline of ARGs. Relatively long duration of ARG changes and high ARGs in the end product of HSAD. Abstract: Livestock manure is a reservoir of antibiotic resistance genes (ARGs). The endogenous inhibitors that emerge during high solid anaerobic digestion (HSAD) greatly influence the bioprocess performance and the ARGs. The effect of endogenous inhibitors including volatile fatty acids (VFAs) and free ammonia (FA) on the ARG occurrences during HSAD of swine manure was investigated in this study. The ARG properties during HSAD (8%–14% total solids (TS)) largely differed from the low TS control (4%). The endogenous inhibitors and microbial communities greatly contributed to the three-phase changes in ARGs. The concentrations of VFAs and abundances of Proteobacteria and int I1 were correlated with the changes in ARGs. FA inhibition and VFA accumulation (especially propionate) delayed and restricted the decline of ARGs. The relatively slow rate of changes in ARGs and high ARGs in the end product suggested the high risk of the HSAD digestate for land application.